2022
DOI: 10.3390/curroncol29020089
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment Patterns and Clinical Effectiveness of Palbociclib Plus an Aromatase Inhibitor as First-Line Therapy in Advanced/Metastatic Breast Cancer: Analysis from the US Syapse Learning Health Network

Abstract: This retrospective single-arm study assessed real-world treatment patterns and clinical outcomes in patients with hormone receptor—positive/human epidermal growth factor receptor 2—negative (HR+/HER2−) advanced/metastatic breast cancer (A/MBC) who received palbociclib plus an aromatase inhibitor as first-line therapy in US community health systems. Using electronic health records from the Syapse Learning Health Network, 242 patients were identified as having received first-line palbociclib plus an aromatase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Additionally, in routine practice, the proportion of patients with dnMBC is much higher than that reported in epidemiological reports, with the number reaching up to 40% of the population observed. [72][73][74][75][76][77][78][79] One of the largest real-world studies derives data from the Flatiron's health longitudinal database, which includes de-identified electronic health records from more than 280 cancer clinics and represents 2.4 million patients with cancer treated in the USA. 72 This retrospective observational study included 1430 patients receiving first-line treatment with palbociclib and letrozole or letrozole alone for MBC from 2015 to 2019.…”
Section: Evidence From Real-world Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in routine practice, the proportion of patients with dnMBC is much higher than that reported in epidemiological reports, with the number reaching up to 40% of the population observed. [72][73][74][75][76][77][78][79] One of the largest real-world studies derives data from the Flatiron's health longitudinal database, which includes de-identified electronic health records from more than 280 cancer clinics and represents 2.4 million patients with cancer treated in the USA. 72 This retrospective observational study included 1430 patients receiving first-line treatment with palbociclib and letrozole or letrozole alone for MBC from 2015 to 2019.…”
Section: Evidence From Real-world Studiesmentioning
confidence: 99%
“…In this subgroup, mPFS was 38.8 months versus 30.5 in patients with rMBC. 77 A single US institution retrospective study including 222 patients with MBC treated with palbociclib and endocrine therapy (mostly AI) from 2015 to 2021 and including 29.7% with dnMBC, showed that this subgroup experienced an improved PFS as compared to those with recurrent disease. 78 In the analysis of the North Carolina University database, an improved PFS of nearly 14 months (25.5 versus 11.9) was observed in patients with dnMBC treated with any first-line therapy, which reached a 19-month difference in the small number of patients treated with CDK4/6i.…”
Section: Evidence From Real-world Studiesmentioning
confidence: 99%
“…Three retrospective studies using data from the Flatiron Health longitudinal database had different study time frames and populations (in terms of patient age); however, there remains a possibility of patient overlap across studies [ 35 , 37 , 52 ]. Older patients were defined as ≥ 60 years of age in one study [ 40 ], ≥ 65 years in 21 studies [ 30 , 32 , 34 , 36 39 , 42 , 43 , 45 , 46 , 49 , 50 , 52 , 53 , 56 58 , 64 , 65 , 68 ], ≥ 70 years in 11 studies [ 31 , 44 , 47 , 48 , 54 , 55 , 59 63 , 66 , 67 ], and ≥ 75 years in four studies [ 33 , 35 , 41 , 51 ]. Three studies evaluated CDK 4/6 inhibitors as a class; however, ≥ 80% of the patients received palbociclib as the CDK 4/6 inhibitor [ 43 , 58 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the included 37 RWE studies, seven included only older patients [ 37 , 41 , 43 , 59 63 ]. Among RWE studies including both younger and older patients, six studies provided data on the proportion of patients aged ≥ 75 years (31% [1960 of 6380]) [ 36 , 37 , 45 , 46 , 51 , 52 ]. Data from a total of 12 studies for patient demographics and baseline characteristics in older patients who received palbociclib were limited and heterogeneous (most studies only described the total patient population).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation